Friedel-Crafts Acylation Of Anisole Catalysed By H-Zeolite Beta Of Crystalline Rice Husk Ash - Ramli, Zainab (Penerbit UTM Press, 2002)
The reactivity of H-Beta zeolite, synthesised directly from crystalline rice husk ash in various SiO2/Al2O3 gel ratios, was studied in the Friedel-Crafts acylation of anisole with propionic anhydride. Reactions were carried out in a batch reactor at various times and reaction temperatures in order to obtain the optimum acylation condition. Products identified by gas chromatography showed that p-methoxypropiophenone is the main product with propionic acid as the main side product. Hbeta catalyst from the SiO2/Al2O3 = 27 gel ratio gave the highest activity, with anisole conversion of 88.9% and product selectivity toward p-ethoxypropiophenone of 75.3%. The optimum acylation condition was taken at 100Â°C reaction temperature in 4 hour reaction. Study showed that acylation reaction follows the electrophilic aromatic substitution mechanism catalysed by BrÃ¸nsted acid sites of H-Beta zeolite.